A combined model of pressure variations in Titan's plasma environment. Issue 24 (29th December 2014) - Achilleos, N.; Arridge, C. S.; Bertucci, C.; Guio, P.; Romanelli, N.; Sergis, N.
Abstract In order to analyze varying plasma conditions upstream of Titan, we have combined a physical model of Saturn's plasma disk with a geometrical model of the oscillating current sheet. During modeled oscillation phases where Titan is farthest from the current sheet, the main sources of plasma pressure in the near‐Titan space are the magnetic pressure and, for disturbed conditions, the hot plasma pressure. When Titan is at the center of the sheet, the main sources are the dynamic pressure associated with Saturn's cold, subcorotating plasma and the hot plasma pressure under disturbed conditions. Total pressure at Titan (dynamic plus thermal plus magnetic) typically increases by a factor of up to about 3 as the current sheet center is approached. The predicted incident plasma flow direction deviates from the orbital plane of Titan by ≲10°. These results suggest a correlation between the location of magnetic pressure maxima and the oscillation phase of the plasma sheet. Our model may be used to predict near‐Titan conditions from "far‐field" in situ measurements.